Assessment of Risk Factors of Polycystic Ovarian Syndrome Among Women: An Online Based Survey: Pharmaceutical Science-Pharmacy practice - Ishrar, S. M. G.; Narayana, Goruntla; Aneesa.K. S, Asma; Priya, Chennampalli; Swetha, Roddam (International Journal of Life Science and Pharma Research, 2023)
Polycystic ovary disorder is a fluctuated and regularly intricate cluster of metabolic and endocrine anomalies. This study aims to assess the risk of PCOS among women aged 15-45 years. This is an online-based cross-sectional survey conducted among women of childbearing age in South India. The data was collected online by providing google links to fill out questionnaire forms by various social media platforms. The questionnaire consists of demographic details and assessment questions. Microsoft Excel was used to interpret data. Statistical analysis done by using chi-square test. A total of 466 women responded, among which the women of 15-25 years and 25-36 years, h 32.46% have hirsutism,22.7% have infertility and overweight problems, 24.7% have mood swings, 49.2% have sleep disturbances, 55.5% have tiredness, 41.9% people have good awareness regarding exercise and lifestyle modifications. This study reveals that there is no proper knowledge about PCOS in the population, especially among girls and women, therefore there is a need to educate the public regarding PCOS at a younger age for better health outcomes.